DEK-AFF2 Carcinoma of the Sinonasal Region and Skull Base: Detailed Clinicopathologic Characterization of a Distinctive Entity. (27th December 2021) - Rooper, Lisa M.; Agaimy, Abbas; Dickson, Brendan C.; Dueber, Julie C.; Eberhart, Charles G.; Gagan, Jeffrey; Hartmann, Arndt; Khararjian, Armen; London, Nyall R.; MacMillan, Christina M.; Palsgrove, Doreen N.; Nix, J. Stephen; et al.
Abstract : A novel DEK-AFF2 fusion was recently reported in 4 nonkeratinizing squamous cell carcinomas of the sinonasal region and skull base, including 1 with exceptional response to immunotherapy, but it is not yet clear if this rearrangement defines a unique clinicopathologic category or represents a rare event. This study aims to characterize a larger cohort of carcinomas with DEK-AFF2 fusions to assess whether they truly constitute a distinctive entity. Among 27 sinonasal and skull base nonkeratinizing squamous cell carcinoma that were negative for human papillomavirus and Epstein-Barr virus, RNA sequencing identified DEK-AFF2 fusions in 13 cases (48%). Nine were centered in the nasal cavity, 2 in the middle ear/temporal bone, 1 in the nasopharynx, and 1 in the orbit. These tumors displayed recurrent histologic features including (1) complex endophytic and exophytic, frequently papilloma-like growth, (2) transitional epithelium with eosinophilic to amphophilic cytoplasm, (3) absent or minimal keratinization with occasional compact keratin pearls, (4) monotonous nuclei, and (5) prominent tumor-infiltrating neutrophils or stromal lymphocytes. This appearance not only overlaps with high-grade basaloid sinonasal carcinomas but also with benign papillomas and tumors reported as low-grade papillary Schneiderian carcinoma. However, DEK-AFF2 carcinomas showed frequent local recurrence, cervical lymph node metastases, and distant metastasis with 2 deaths from disease, confirming they are aggressive malignancies despite relatively bland histology. Overall, the distinctive molecular, histologic, and clinical features of DEK-AFF2 carcinomas suggest they represent a unique entity in the sinonasal region. This tumor merits increased pathologic recognition to better understand its prognostic and therapeutic implications.